PENERAPAN MEDIA DIGITAL SMART TV PADA MATERI PAI (PENDIDIKAN AGAMA ISLAM) DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMP AL FURQON MADRASATUL QUR’AN TEBUIRENG JOMBANG - Ibrohim, Ali Achmad; Ali Said (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the implementation of digital smart TV media in Islamic Religious Education (PAI) instruction and this effect on student learning motivation at Al Furqon Madrasatul Qur’an Junior High School, Tebuireng Jombang. Departing from the observed problem of low student engagement during conventional instruction, the research aims to describe the systematic implementation of Smart TV, analyse its role in enhancing learning motivation, and identify factors that support or inhibit its effectiveness. A qualitative approach with a case study design was employed. Data were gathered through observation, in-depth interviews with the school principal, vice-principal for curriculum, PAI teacher, and students, and document analysis. Data analysis followed the Miles and Huberman model, data reduction, data display, and conclusion drawing, with validity ensured through technical, source, and time triangulation. Findings reveal that Smart TV implementation across four systematic stages, planning, execution, student engagement, and evaluation, produced more effective and interactive learning compared to conventional projectors. Audio-visual content delivery through Smart TV demonstrably heightened student attention, willingness to ask questions, and enthusiasm, all of which are indicators of learning motivation as conceptualised by Hamzah B. Uno. Key supporting factors include proactive school policy, classroom-level facility availability, and a relatively young, tech-literate teaching staff; inhibiting factors encompass unstable internet connectivity, uneven utilisation among teachers, and periodic device maintenance demands. The study concludes that Smart TV constitutes an effective pedagogical instrument for improving PAI learning quality, provided its implementation is accompanied by adequate teacher competence and sustained infrastructural support.